Strategy for promoting photovoltaics in urban areas: lessons from the first grid connected residential house in UK - Fuentes, M.; Roaf, S. (Avances en Energías Renovables y Medio Ambiente - AVERMA, 2022)
The building of the first integrated photovoltaic roof on a house in Britain, the Oxford Solar House (OSH) has had a significant impact on the perception of the viability of PVs on homes in the UK. It also provided many lessons on the possible barriers that may be encountered in the development of an internal domestic PV industrv . These inelude technical, institutional, management and marketing barriers, which are discussed in this paper.